Inflammation condition sensitizes Piezo1 mechanosensitive channel in mouse cerebellum astrocyte - Yu, Donggyeom; Ahmed, Ajan; Jayasi, Jazmine; Womac, Andres; Sally, Olajuwon; Bae, Chilman (Frontiers in Cellular Neuroscience, 2023)
Piezo1 mechanosensitive ion channel (MSC) plays a significant role in human physiology. Despite several research on the function and expression of Piezo1 in the nervous system, its electrophysiological properties in neuroinflammatory astrocytes remain unknown. We tested whether astrocytic neuroinflammatory state regulates Piezo1 using electrical recordings, calcium imaging, and wound healing assays on cultured astrocytes. In this study, we determined whether neuroinflammatory condition regulates astrocytic Piezo1 currents in astrocytes. First, we performed electrophysiological recordings on the mouse cerebellum astrocytes (C8-S) under lipopolysaccharide (LPS)-induced neuroinflammatory condition. We found that LPS treatment significantly increased MSC currents in C8-S. The half-maximal pressure of LPS treated MSC currents was left-shifted but the slope sensitivity was not altered by LPS treatment. LPS-induced increase of MSC currents were further augmented by Piezo1 agonist, Yoda1 but were normalized by Piezo1 inhibitor, GsMTx4. Furthermore, silencing Piezo1 in LPS treated C8-S normalized not only MSC currents but also calcium influx and cell migration velocity. Together, our results show that LPS sensitized Piezo1 channel in C8-S astrocytes. These findings will suggest that astrocytic Piezo1 is a determinant of neuroinflammation pathogenesis and may in turn become the foundation of further research into curing several neuronal illnesses and injury related inflammation of neuronal cells.